(untitled) (Medico Legal Update, 2020)
Background: Epidemiologically speaking the diabetes mellitus is one of the common leading causes of mortality and morbidity worldwide. Prognosis of the disease is variable and depends on the development of macrovascular and microvascular complications. Researchers are nowadays spending plenty of time trying to identify prognostic factors in order to make treatment approach be tailored according to the predictive value of such prognostic factors. One of these newly introduced factors is red cell distribution width (RDW). Aim of the study: The current study was aiming at shedding light of the possible prognostic role of RDW in patients with type 1 and 2 diabetes mellitus. Patients and methods: The present case control study was carried out at diabetes center in Al-Diwaniayh Teaching Hospital, Al-Diwaniyah Province, Iraq. The study started on January 2019 and ended on August 2019. The study included 30 patients with established diagnosis of type 2 diabetes mellitus, 30 patients with type 1 diabetes mellitus and 30 apparently healthy control subjects. Diabetic patients were selected randomly from the pool of patients already registered in that center. Results: We grouped diabetic patients into two groups according to HbA1c level, ?7% and > 7% and contrasted hematological levels between those new groups. The results showed no significant difference in mean hematological values between the two groups in diabetic type 1 and type 2 patients (P > 0.05). Conclusion: There was no significant role for RDW in predicting poor glycemic control of patients with type 1 or type 2 diabetes mellitus.